La Tinta Bay, Trinidad - (:unkn) unknown (Davidson and Todd,[Trinidad and Tobago], 2011)
The postcard shows La Tinta Bay, a popular beach on the island of Chacachacare, the westernmost of the Bocas Islands which belong to Trinidad and Tobago.
Colour: Sepia with Hues of Green; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; [1907]; Bays--Trinidad and Tobago; Islands--Trinidad and Tobago; Beaches--Trinidad and Tobago; Beachgoers--Trinidad and Tobago; Chacachacare